The watchman - Crais, Robert (Crais, Robert. Joe Pike novel., 2011)
Working as a bodyguard for a spoiled federal witness, Joe Pike hatches a desperate plan to disappear with the woman in the underworld of Los Angeles and turn on her would-be killers, an effort in which he enlists the help of private investigator Elvis Cole.